'Arcobacter porcinus' sp. nov., a novel Arcobacter species uncovered by Arcobacter thereius. (January 2017) - Figueras, M.J.; Pérez-Cataluña, A.; Salas-Massó, N.; Levican, A.; Collado, L.
Abstract: Arcobacter thereius is a species associated with human disease. A group of A. thereius pork strains (represented by strain LMG 24487) clustered separately from the type strain (LMG 24486 T ) in the 16S rRNA and multilocus phylogenetic trees. In silico DNA-DNA hybridization and average nucleotide identity results between their genomes (93.3 and 51.1%) confirmed ' Arcobacter porcinus ' (LMG 24487 T ) as a new species.